2008
DOI: 10.1080/17482960701856300
|View full text |Cite
|
Sign up to set email alerts
|

Design, power, and interpretation of studies in the standard murine model of ALS

Abstract: Identification of SOD1 as the mutated protein in a significant subset of familial amyotrophic lateral sclerosis (FALS) cases has led to the generation of transgenic rodent models of autosomal dominant SOD1 FALS. Mice carrying 23 copies of the human SOD1(G93A) transgene are considered the standard model for FALS and ALS therapeutic studies. To date, there have been at least 50 publications describing therapeutic agents that extend the lifespan of this mouse. However, no therapeutic agent besides riluzole has sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
410
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(424 citation statements)
references
References 35 publications
11
410
0
1
Order By: Relevance
“…Neurological evaluation of mSOD1 G93A mice was assessed (3 times weekly from 15 weeks of age) employing the ALS Therapy Development Institute neurological score system proposed by Scott et al [26]: 0 = full extension of hindlimbs away from lateral midline when mouse is suspended by its tail; 1 = collapse or partial collapse of leg extension towards lateral midline (weakness) or trembling of hindlimbs during tail suspension; 2 = during walking any part of foot is dragging along table (walk with enlarged posterior train); 3 = rigid paralysis or minimal joint movement, foot not being used for forward motion; 4 = mouse cannot right itself within 30 s from either side. For the data analysis, dead mice were included in category B4^.…”
Section: Neurological Score Evaluationmentioning
confidence: 99%
“…Neurological evaluation of mSOD1 G93A mice was assessed (3 times weekly from 15 weeks of age) employing the ALS Therapy Development Institute neurological score system proposed by Scott et al [26]: 0 = full extension of hindlimbs away from lateral midline when mouse is suspended by its tail; 1 = collapse or partial collapse of leg extension towards lateral midline (weakness) or trembling of hindlimbs during tail suspension; 2 = during walking any part of foot is dragging along table (walk with enlarged posterior train); 3 = rigid paralysis or minimal joint movement, foot not being used for forward motion; 4 = mouse cannot right itself within 30 s from either side. For the data analysis, dead mice were included in category B4^.…”
Section: Neurological Score Evaluationmentioning
confidence: 99%
“…However, when all cohorts tested were combined, mean survival was significantly extended by 14 and 9 days when compared with nontreated and VSVG IGF‐1 LV‐treated control cohorts, respectively. Although our sample size was sufficient to detect a medium effect with 80% power, our observations further demonstrate the necessity of including large animal numbers in order to detect meaningful therapeutic effect 26. Variability reported in our study may be attributed to a number of factors such as: (i) the delivery strategy, as muscle injection cannot by principle be accurate as far as the injection point and depth is concerned, (2) the given dose used, as only 50% of particles injected are expected to be functional,22 or (3) even the strength of expression of the transgene itself, which is controlled by a CMV enhancer/promoter.…”
Section: Discussionmentioning
confidence: 70%
“…A priori power analysis revealed that 12 animals per group (both males and females) was a sufficient sample size in order to detect a medium effect with 80% power 26. Transgenic mice were genotyped according to the Jackson Laboratory protocols and were organized in subgroups of 18 (6 animals per group; (i) no treatment or mock ( α CAR eGFP LV), (ii) α CAR IGF‐1 LV, (iii) VSVG IGF‐1 LV), and they were age matched and litter matched wherever possible.…”
Section: Methodsmentioning
confidence: 99%
“…This mouse is genetically engineered to express multiple copies of the mutant human SOD1 gene, an etiological factor in a portion of patients with familial ALS (Kenna et al, 2013). In line with critical appraisal of this aggressive model (Scott et al, 2008), it is increasingly recognized that readouts such as rotarod performance and body weight may be more indicative predictors of therapeutic benefit than survival (Knippenberg et al, 2010;Scott et al, 2008). Our results show that JAK4D treatment elicits statistically M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT significant and clinically-relevant positive effects in these two important functional measures of therapeutic benefit in G93A-SOD1 mice, accompanied by attenuation of neuronal loss in lumbar spinal cord.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%